2012
DOI: 10.1371/journal.pone.0048665
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Nicotine and Antagonism of β2 Subunit Containing Nicotinic Acetylcholine Receptors Have Similar Effects on Affective Behavior in Mice

Abstract: Nicotine leads to both activation and desensitization (inactivation) of nicotinic acetylcholine receptors (nAChRs). This study tested the hypothesis that nicotine and a selective antagonist of β2*nAChRs would have similar effects on affective behavior. Adult C57BL/6J male mice were tested in a conditioned emotional response (CER) assay which evaluates the ability of an aversive stimulus to inhibit goal-directed behavior. Mice lever-pressed for a saccharin reinforcer according to a variable schedule of reinforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 124 publications
4
37
1
Order By: Relevance
“…While we are not aware of brain imaging studies linking HA with nAChR availability, a prior behavioral genetics study found links between single nucleotide polymorphisms within the nAChR α4 subunit gene (CHRNA4) and HA (Roe et al, 2009), providing additional evidence for the mediation of HA by the cholinergic system. Furthermore, the findings here are consistent with prior research which demonstrates that the cholinergic system is linked with potentiation of a broad range of adaptive behaviors to environmental stimuli (Picciotto et al, 2012), which includes nAChR mediation of fear-like responses (Davis and Gould, 2007; Anderson and Brunzell, 2012), and also includes influences on attention, food intake, and affect.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While we are not aware of brain imaging studies linking HA with nAChR availability, a prior behavioral genetics study found links between single nucleotide polymorphisms within the nAChR α4 subunit gene (CHRNA4) and HA (Roe et al, 2009), providing additional evidence for the mediation of HA by the cholinergic system. Furthermore, the findings here are consistent with prior research which demonstrates that the cholinergic system is linked with potentiation of a broad range of adaptive behaviors to environmental stimuli (Picciotto et al, 2012), which includes nAChR mediation of fear-like responses (Davis and Gould, 2007; Anderson and Brunzell, 2012), and also includes influences on attention, food intake, and affect.…”
Section: Discussionsupporting
confidence: 90%
“…In one such study, inactivation of β2*-containing nAChRs with a specific receptor antagonist reduced fear-like and anxiety-like behavior in rodents (Anderson and Brunzell, 2012). Similarly, β2*-containing nAChRs have been shown to be critical for the nicotine-induced enhancement of contextual fear conditioning (Wehner et al, 2004; Davis et al, 2007) and to mediate the anxiety-like and affective components of nicotine withdrawal (Jackson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The β2*nAChR antagonist, DHβE, and partial agonists varenicline, ABT-089 and sazetidine promote anxiolysis-like behavior in the EPM, marble burying and conditioned inhibition tasks [129132]. Low dose nicotine mimics anxiolysis-like effects of DHβE, suggesting that desensitization of nAChRs by low doses of nicotine may decrease anxiety [130]. A study using mice lacking nAChR α4 subunits in the VTA showed that these mice failed to benefit from the anxiolytic-like effects of low dose nicotine, suggesting that α4β2*nAChRs in the VTA are required for nicotine-induced anxiolysis in the EPM [91] (but see [133]).…”
Section: Nachr Contributions To Addiction Phenotype: Animal Modelsmentioning
confidence: 99%
“…In contrast, acute administration of varenicline at a range of doses (0.01, 0.1, or 1.0 mg/kg) did not ameliorate nicotine withdrawal behaviors in the NIH test (Figure 3b). To evaluate the effects of these drugs in another model of anxiety, we utilized the marble-burying test, which has been shown to be sensitive to both acute and chronic administration of nicotinic compounds in drug-naive animals (Anderson and Brunzell, 2012;Turner et al, 2010Turner et al, , 2011. In this task, we observe that treatment with sazetidine-A (0.1 mg/kg) as well as varenicline (1.0 mg/kg) significantly reduces the number of marbles buried in this task compared with animals undergoing 24 h WD (Figure 3c).…”
Section: Effects Of Sazetidine-a and Varenicline In The Nih Test And mentioning
confidence: 99%